2008
DOI: 10.1111/j.1439-0531.2007.00918.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Immunolocalization of Heat Shock Proteins (Hsp)‐60, ‐70, ‐90 in Boar, Stallion, Dog and Cat Spermatozoa

Abstract: Heat shock proteins (Hsp)-60, -70 and -90 are important testis chaperones that fulfil several functions during sperm cell maturation. In post-meiotic cells, their expression may change or may be undetectable and in some species it may be evident in mature spermatozoa. The aims of this study were to verify whether Hsp60, -70 and -90 are present in the sperm, and to compare their localization in boar, stallion, cat and dog spermatozoa by immunofluorescence. Hsp-60 immunoreactivity was detected in sperm midpiece … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 43 publications
(76 reference statements)
5
35
1
1
Order By: Relevance
“…These results differ from those showing HSP60 immunoreactivity in boar, stallion, dog, and cat spermatozoa at mitochondrial positions (Volpe et al 2008). However, they are in agreement with the acrosomal HSP60 localization observed in mouse spermatozoa (Asquith et al 2004).…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…These results differ from those showing HSP60 immunoreactivity in boar, stallion, dog, and cat spermatozoa at mitochondrial positions (Volpe et al 2008). However, they are in agreement with the acrosomal HSP60 localization observed in mouse spermatozoa (Asquith et al 2004).…”
Section: Discussioncontrasting
confidence: 67%
“…Moreover, our data demonstrate the presence of HSC70 in rabbit spermatids. Although no direct evidence is available concerning the presence of HSC70 in spermatids, many investigations have demonstrated the localization of HSP70 immunolabeling in spermatozoa (Matwee et al 2001;Spinaci et al 2005;Volpe et al 2008).…”
Section: Discussionmentioning
confidence: 98%
“…The presence of HSP70 and HSP90 proteins in porcine spermatozoa has been described as playing a role in sperm-oocyte interaction and sperm motility respectively (Huang et al 2000b;Spinaci et al 2005;Volpe et al 2008). No correlation between HSP70 and semen quality was found (Turba et al 2007) while HSP90 was investigated only in relation to the quality of cryopreserved semen (Wang et al 2014;Zhang et al 2015).…”
Section: Introductionmentioning
confidence: 97%
“…Several HSPs, including HSP60, HSP90 and HSP70, undergo phosphorylation during capacitation. [28][29][30][31][32][33][34] Recent evidence has shown that HSP60 and HSP90 (ERp99 and Grp94) migrate to the surface of the sperm head during capacitation, in concert with the ability of sperm to bind to the egg. In addition, although circumstantial, it was interesting to note that the only tyrosine-phosphorylated sperm heads were able to bind to the zona pellucida.…”
Section: The Secrets Of a Silent Cellmentioning
confidence: 99%